An assessment of the critical human, financial, and institutional capacity issues affecting West African agricultural R&D: Synthesis and policy considerations - Beintema, Nienke M.; Stads, Gert-Jan (International Food Policy Research Institute, 2014)
This current synthesis highlights the cross-cutting trends and challenges that emerged from the country-level data for West Africa, structuring it within five broad areas: funding capacity, human resource capacity, research outputs, research-related infrastructure, and institutional conditions-all in terms of whether they support or impede the effective and efficient conduct of agricultural R&D. This report concludes with a set of national and regional policy recommendations for ECOWAS’s Council of Ministers of Agriculture, national-level decisionmakers, and other stakeholders.